Elevational gradients in constitutive and induced oak defences based on individual traits and their correlated expression patterns. Issue 3 (21st December 2020) - Galmán, Andrea; Abdala‐Roberts, Luis; Wartalska, Pola; Covelo, Felisa; Röder, Gregory; Szenteczki, Mark A.; Moreira, Xoaquín; Rasmann, Sergio
Abstract : Elevational gradients are useful ecological settings for revealing the biotic and abiotic drivers of plant trait variation and plant–insect interactions. However, most work focusing on plant defences has looked at individual traits and few studies have assessed multiple traits simultaneously, their correlated expression patterns, and abiotic factors associated with such patterns across elevations. To address this knowledge gap, we studied elevational variation in direct (phenolic compounds) and indirect (volatile organic compounds) constitutive defences and their inducibility after feeding by a specialist beetle Altica quercetorum in saplings of 18 wild populations of Quercus pyrenaica . We tested for: 1) clines in each defensive trait individually, 2) their patterns of correlated expression and 3) associations between any such clines and climatic factors. We found that constitutive direct defences (lignins and hydrolysable tannins) decreased with increasing elevation. We observed no elevational gradient for constitutive indirect defences (volatile organic compounds) or the inducibility of direct or indirect defensive traits when looking at groups of compounds. However, at individual tree‐level, increased induction of two monoterpenes (α‐fenchene and camphene) at higher elevation was shown. Furthermore, we show a significant pattern of co‐expression of constitutive and induced phenolics across populations, which weakened with increasing elevation. Finally, we found no evidence that climatic factors were associated with either individual or correlated trait expression patterns across elevations. Overall, these findings call for moving beyond elevational clines in individual plant defences, and argue that assessing elevational shifts in trait correlated expression patterns and their underlying mechanisms can increase our understanding of plant defence evolution and plant–herbivore interactions along environmental gradients.